Laparoscopic Ventral Hernia Repair Combined with Sleeve Gastrectomy in Morbidly Obese Patients: Early Outcomes - Marzouk, Ahmed M.S.M.; Ali, Heba O.E. (The Surgery Journal, 2019)
Background Morbid obesity is a serious chronic condition with, among other symptoms, increased intra-abdominal pressure and subsequent abdominal wall hernias. The optimal management of these manifestations is still controversial. The objective of this study was to assess the early postoperative outcomes of a surgical approach combining laparoscopic ventral hernia repair (LVHR) with sleeve gastrectomy in morbidly obese patients.Methods In this retrospective study, we reviewed the files of patients who are obese with a primary ventral hernia of less than 10 cm in diameter who received simultaneous laparoscopic sleeve gastrectomy and LVHR at our institution between February 2016 and July 2018. LVHR was performed using an intraperitoneal only mesh. The individual mesh size was chosen based on the number and size of the defects. Clinical and radiological follow-ups were performed between 9 and 15 months.Results A total of 15 patients were included. Five of them were males. The mean body mass index was 45.2 kg/m2 (range: 38.7–56.2 kg/m2). The mean hernia defect size was 2.6 cm (range: 1.3–4.2 cm). Mesh size was 10 × 15 cm in five, 20 × 15 cm in seven, and 25 cm× 20 cm in three patients. All patients were discharged without complications on the second postoperative day. Mean follow-up was at 12 months. One patient presented with hernia recurrence 14 months after surgery and four patients presented with self-limited seroma.Conclusion Despite ambiguous guidelines and ongoing debate regarding simultaneous bariatric surgery and ventral hernia repair, the short-term outcomes of this approach appeared promising, provided that patients are carefully selected and receive an individually tailored approach.
Keywords: hernia; laparoscopic ventral hernia repair; morbid obesity; sleeve gastrectomy